PENGARUH DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN TANAMAN SAWI (BRASSICA JUNCEA L.) - Gole, Imelda Dada; Sukerta, I Made; Udiyana, Bagus Putu (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
Efffect of cow manure dosage on the growth of mustard plants (Brassica juncea L.). This study aims to determine the effect of cow manure doses on the growth of mustard greens. This research was conducted from 15 December 2018 to 26 January 2019,in the Kalpataru garden. SedapMalam, East Denpasar. This study used a randomized block design (RBD) with 6 treatments and 4 replications. The treatment of cow manure dosage consists of D1 (20g), D2 (40g), D3 (60g), D4 (80g), D5 (100g) and D0 (control). Each treatment was repeated 4 times so that there were 24 experimental units. Observations made were plant height, leaf number, leaf area, stem circumference, fresh weight and oven dry weight. The results showed that the doses of cow manure had a very significant effect on all parameters. From the manure doses studied, it was found that the growth of mustard plants was best found at doses of cow manure with a dose of 100 gr / polybag.